KARAKALPAK FILM HISTORY (Proceedings of International Educators Conference, 2024)
Nukus filiali о‘qituvchisiAnnotation: This article analyzes the cultural significance of films, specifically feature films shot at the "Karakalpakfilm" film studio. It explores the role of these films in youth culture, the importance of direction and storytelling, and the skills of actors.